Metro rail projects in India a study in project planning - Ramachandran, M., 1950- (New Delhi ; Oxford : Oxford University Press, 2012)
The metro rail system introduced in Indian cities in recent years has resulted in significant improvements in the country's transportation infrastructure. This study maps the story of India's largest transit system and uses data and first-hand information to provide an analysis of the urban transport scenario in Indian cities.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Subways -- India; Railroads -- India; Local transit -- India; Project management -- India